Black or white is not always delineated: The influence of moral disengagement and clawbacks on the intention to manipulate accrual earnings and real activity - Ratna Candra Sari; Mahfud Sholihin; Zuhrohtun Zuhrohtun; Ida Ayu Purnama; Umi Syafaatul Udhma (Cogent Business & Management, 2023)
The purpose of this study is to examine the effectiveness of clawback to minimize earnings management due to moral disengagement tendencies. To understand the phenomenon of earnings manipulation, as well as the propensity for moral disengagement, we turn to the agency theory and the social cognition theory. In addition, clawback is explained by the supernatural monitoring hypothesis as a tool to lessen earnings manipulation. To test the hypotheses, an experimental study was conducted using a within-subject design. The participants were professional accountants who were pursuing master's level studies. We found that moral disengagement is preceded by an ethical orientation. More importantly, we found the impact of ethical orientation on intentions for managing earnings is mediated by moral disengagement. Further, we found the clawback scheme reduces the effect of moral disengagement on intentions to manipulate earnings. More specifically, the results show that when adopting a clawback strategy, moral disengagement significantly increases the intention to manipulate accruals but does not significantly affect the intention to manipulate real activity. The results suggest that seriously considering individual characteristics and implementing appropriate incentive programs may lead to a high standard of financial reporting.
Keywords: 650; accrual manipulation; clawback; moral disengagement; real activity manipulation; social cognition theory